2020
DOI: 10.3390/ma13194283
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization of Multiwalled Carbon Nanotubes: Numerical Simulation Study

Abstract: The elastic properties of armchair and zigzag multiwalled carbon nanotubes were investigated under tensile, bending, and torsion loading conditions. A simplified finite element model of the multiwalled carbon nanotubes, without taking into account the van der Waals interactions between layers, was used to assess their tensile, bending, and torsional rigidities and, subsequently, Young’s and shear moduli. Relationships between the tensile rigidity and the squares of the diameters of the outer and inner layers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…All CNTs exhibited an interlayer spacing ranging from 0.335 to 0.342 nm. This can indicate the type of the CNT, and for this interlayer distance, the armchair type is associated [1,[47][48][49]. Numerical simulation studies revealed that the MWCNT structure has an influence on the mechanical properties.…”
Section: Characterization Of the Cntsmentioning
confidence: 98%
See 2 more Smart Citations
“…All CNTs exhibited an interlayer spacing ranging from 0.335 to 0.342 nm. This can indicate the type of the CNT, and for this interlayer distance, the armchair type is associated [1,[47][48][49]. Numerical simulation studies revealed that the MWCNT structure has an influence on the mechanical properties.…”
Section: Characterization Of the Cntsmentioning
confidence: 98%
“…Numerical simulation studies revealed that the MWCNT structure has an influence on the mechanical properties. For instance, Sakharova et al [1] concluded by numerical simulation that this armchair carbon nanotube structure presents a slightly higher Young's and shear moduli compared with zigzag-structured ones, which can be an advantage of using them as reinforcement. In nanocomposite production, the structure of the CNTs can affect their final properties.…”
Section: Characterization Of the Cntsmentioning
confidence: 99%
See 1 more Smart Citation
“…We subsequently observed the formation of surficial nanostructures, which increased in size with multiple curved layers, separated ∼0.36 nm apart, indicative of graphitic carbon in the form of MWCNTs. 25 Figure 2 provides a TEM image of the small SiC grain (experiment 1) with the curved MWCNT coating. The inset shows a TEM image of a MWCNT displayed for comparison.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The C=C covalent bond formed by sp 2 hybridization is one of the strongest covalent bonds in nature, so carbon nanotubes have extremely high mechanical properties [ 14 , 15 ]. The elastic modulus of CNTs can reach 1TPa, which is almost the same as that of diamond and about five times that of steel [ 16 ]. However, due to their high cohesion, CNTs are prone to form intertangled cluster structures, which hinders their effective dispersion in a TPI matrix [ 17 ].…”
Section: Introductionmentioning
confidence: 99%